2016
DOI: 10.1159/000450791
|View full text |Cite
|
Sign up to set email alerts
|

Nail Damage (Severe Onychodystrophy) Induced by Acrylate Glue: Scanning Electron Microscopy and Energy Dispersive X-Ray Investigations

Abstract: Background: Scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) techniques have been used in various fields of medical research, including different pathologies of the nails; however, no studies have focused on obtaining high-resolution microscopic images and elemental analysis of disorders caused by synthetic nails and acrylic adhesives. Methods: Damaged/injured fingernails caused by the use of acrylate glue and synthetic nails were investigated using SEM and EDX methods. Results: SEM and EDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…One study imaged with electron microscopy and obtained an elemental analysis of a healthy fingernail versus a fingernail that been exposed to synthetic nails and acrylic glue. Compared to the flat, uniform appearance of a healthy nail, the exposed nails were rough with globular areas [68]. Furthermore, elemental analysis revealed that nail glue causes degradation of disulfide bridges in the nail matrix, effectively destabilizing the matrix and causing roughness and loss of uniformity.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…One study imaged with electron microscopy and obtained an elemental analysis of a healthy fingernail versus a fingernail that been exposed to synthetic nails and acrylic glue. Compared to the flat, uniform appearance of a healthy nail, the exposed nails were rough with globular areas [68]. Furthermore, elemental analysis revealed that nail glue causes degradation of disulfide bridges in the nail matrix, effectively destabilizing the matrix and causing roughness and loss of uniformity.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, elemental analysis revealed that nail glue causes degradation of disulfide bridges in the nail matrix, effectively destabilizing the matrix and causing roughness and loss of uniformity. The glue also diminished the amount of silicon and aluminum in the nail, decreasing the brightness and hardness of the nail [68].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this work is to evaluate the status quo, as evidenced by expert opinions in the field, to narrow the topic, and to isolate and underline the impact of these tools on the resulting architectures and following bio-related potential. Although our research spans diverse topics, from bioagents’ carriers, biosynthesis [ 9 , 10 , 11 ], genotypic mapping [ 12 , 13 , 14 , 15 , 16 ], and cell growth [ 17 , 18 ], to artificial water channels [ 19 , 20 , 21 , 22 ], and the exploration of investigative methods [ 23 , 24 ], the review considers the hot topics of drug and gene delivery, antioxidants development, and bioimaging. We addressed these topics by following five major themes: (i) temperature- and pH-responsive systems; (ii) glycodynameric frameworks; (iii) polymeric non-viral vectors; (iv) metallic nanoconjugates; and, (v) smart organic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Nails, like hairs, have been subjected to variety of onslaughts. [2] The nail changes may be an early sign of skin and systemic diseases and sometimes nails only may be affected. Thus examination of nails becomes necessary in each and every case.…”
Section: Introductionmentioning
confidence: 99%